Comparison of nerve growth factor-induced sensitization pattern in lumbar and tibial muscle and fascia - Weinkauf, Benjamin; Obreja, Otilia; Hoheisel, Ulrich; Mense, Siegfried; Schmelz, Martin; Rukwied, Roman (Muscle & nerve, 2014)
Introduction: Nerve growth factor (NGF) induces profound hyperalgesia. In this study we explored patterns of NGF sensitization in muscle and fascia of distal and paraspinal sites. Methods: We injected 1 µg of NGF into human (n = 8) tibialis anterior and erector spinae muscles and their fasciae. The spatial extent of pressure sensitization, pressure pain threshold, and mechanical hyperalgesia (150 kPa, 10 s) was assessed at days 0.25, 1, 3, 7, 14, and 21. Chemical sensitization was explored by acidic buffer injections (pH 4, 100 µl) at days 7 and 14. Results: The mechanical hyperalgesia area was larger in tibial fascia than in muscle. Pressure pain thresholds were lower, tonic pressure pain ratings, and citrate buffer evoked pain higher in fascia than in muscle. Conclusions: Spatial mechanical sensitization differs between muscle and fascia. Thoracolumbar fasciae appear more sensitive than tibial fasciae and may be major contributors to low back pain, but the temporal sensitization profile is similar between paraspinal and distal sites.
Gesehen am 21.02.2018